Diagnostics and updated checklist of Oriental Pseudopostega (Opostegidae), including the matrona species group with a new, extralimital species discovered in the Mediterranean - Stonis, Jonas R.; Remeikis, Andrius; Solis, M. Alma; Karsholt, Ole (Zootaxa, 2021)
We provide diagnostics for eight species groups of Oriental Pseudopostega Kozlov (Lepidoptera: Opostegidae) and a pictorial key for their identification. We designate three new species groups, P. frigida and P. strigulata groups, and the P. auritella group for two Palaearctic species, and rename the P. nigrimaculella group as the P. matrona group. We assign P. euryntis (Meyrick), P. zelopa (Meyrick), and P. subviolaceae (Meyrick), three formerly unplaced species, to species groups based on re-examination of male and female genitalia. We list 22 currently known Oriental Pseudopostega species, and synonymize Pseudopostega spilodes (Meyrick), syn. nov., with P. machaerias (Meyrick). One new Mediterranean species with affiliations to the Oriental fauna, P. matrona Karsholt & Remeikis, sp. nov., is described. The new species is illustrated with photographs of the adults and male genitalia. Additionally, we provide a distribution map of the P. matrona group, now extralimital to the Oriental region.